2019
DOI: 10.3389/fonc.2019.00479
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy, Safety, and Costs of Sorafenib vs. Sunitinib as First-Line Therapy for Metastatic Renal Cell Carcinoma: A Systematic Review and Meta-Analysis

Abstract: Purpose: Sorafenib and sunitinib are extensively used as first-line medications for metastatic renal cell carcinoma (mRCC). This meta-analysis was conducted to assess the antitumor efficacy, toxicity, and costs of the two drugs among mRCC patients. Materials and methods: PubMed, ScienceDirect, Scopus, Web of Science, Ovid MEDLINE, the Cochrane Library, Embase, and Google Scholar were searched for eligible articles. The endpoints consisted of progression-free survival (PFS), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…However, whether PGK1 is related to the resistance of tumor cells to TKI drugs has not been reported. Sorafenib, as a TKI drug, is still the first-line treatment for advanced RCC [ 37 ]. Our experiments confirmed that sorafenib inhibited Raf/MEK/ERK signaling pathway in all three KIRC cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether PGK1 is related to the resistance of tumor cells to TKI drugs has not been reported. Sorafenib, as a TKI drug, is still the first-line treatment for advanced RCC [ 37 ]. Our experiments confirmed that sorafenib inhibited Raf/MEK/ERK signaling pathway in all three KIRC cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At present, sorafenib is the first-line drug for RCC [ 37 ], but patients with advanced RCC resistant to sorafenib have limited clinical treatment options. So far, exploring sorafenib resistance mechanism in RCC is to find therapeutic targets for coping with this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Since RCC is an angiogenic disease, a promising avenue of treatment is to block angiogenesis, thereby suppressing the supply of oxygen and nutrients to the tumor. Initially, the anti-angiogenic activity of the tyrosine kinase inhibitor (TKI) sunitinib extends the progression-free survival of patients [3], but resistance occurs during treatment [4]. Thus, therapy resistance is one, if not the main, problem, in treating advanced RCC.…”
Section: Introductionmentioning
confidence: 99%
“…However, sunitinib is more toxic than sorafenib. In Asian patients, sorafenib may be more appropriate than sunitinib ( Deng et al, 2019 ). Therefore, we conducted a study on sorafenib-resistant clear cell renal cancer.…”
Section: Introductionmentioning
confidence: 99%